Compare the Cost per Serving - Jennifer Hillan; Claudia Peñuela (EDIS)
To find the best buy on certain foods, like meat, it’s important to compare the cost per serving. This revised 2-page fact sheet includes a table with servings per pound of various beef and chicken cuts, as well as examples of how to determine the price per serving. Written by Jennifer Hillan and Claudia Peñuela and published by the UF Department of Family Youth and Community Sciences, June 2011. (UF/IFAS Photo by Tom Wright)